Diseño e instalación de un tablero didáctico para la programación de MINIPLC SIEMENS con logo. - Macas León, Janela Patricia (2009)
The boards designed for the SIEMENS MINIPLC Programming with Logo !, basically have been made in order to facilitate to the student the execution of practices of Automation and Control of Motors by elements that are easy to manipulate. With the present Practical Work we have seen how basic the MINIPLC have become in the electrical industry since they solve easily presented problems in the techniques of installations. The display and programming of the MINIPLC can be done quite simply thanks to the small LCD display on the front of the MINPLC. The implementation of this equipment will give the students the opportunity to improve their knowledge either in the Control of Motors or in the application of MINIPLC in electrical, electronic and electromechanical fields